Adipocytes in breast cancer: lipolytic and mitochondrial alterations in the tumor microenvironment - Pagnotta, Priscila Ayelén (2020)
Breast cancer cells induce metabolic reprogramming of peritumoral adipocytes, promoting adipocyte delipidation and atrophy/regression. We have previously reported that peritumoral adipocytes showed a decrease in the expression of Plin1, which together with HSL and ATGL regulate the lipolytic process, and smaller lipid droplet size.